Management of Primary Herpetic Gingivostomatitis in Children: Case Report - Hidayatullah, Taufiqi; Ossa, Yuli Fatzia (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Primary herpetic gingivostomatitis is a common condition of oral disease in children. Lesions are generally found on the mucous lips, tongue, cheeks, even on the palatal mucosa. Primary herpetic gingivostomatitis is triggered by infection with Herpes Simplex Virus (HSV) type 1. The diagnosis and treatment of this oral disease are often wrong because proper history is not explored and treatment seems successful due to the self-limiting nature of this lesion. Objective: This paper reports 2 cases of gingivostomatitis in different children, with the same diagnosis but different treatment. Materials and Methods: There were 2 cases, a 12-year- old and 10 year-old boy comes with his parents to the dentist, then introduces the patient to the case and performs a clinical examination followed by anamnesis and diagnosis. The examination results lead to a similar diagnosis but the clinical signs and treatment are slightly different. Results: Accurate history and clinical examination are necessary for appropriate therapy. In these two cases, one child only received palliative care and the other required supportive care. Education about viral transmission to parents is one of the keys to successful treatment. Conclusion: Primary herpetic gingivostomatitis affects youngsters. Vesicles and mouth ulcerations may precede this virus-caused sickness. Clinical factors and patient needs determine causal, symptomatic, palliative, and supportive therapy for this instance.